The Effectiveness of a Developed Generative, Cognitive and Constructive Model in Improving Computer Programming Skills and Self – Efficiency Beliefs among 9th Grade Female Students in Jordan - Al-Ar’ar, Ghada Mahmoud; Abass, Harith Abood (Journal of Educational and Psychological Sciences, 2022)
This study aimed to investigate the effectiveness of an improved generative, cognitive and constructive model on improving computer programming skills and developing self-efficacy beliefs among ninth grade female students in Jordan. The participants of the study consisted of 80 female students who were randomly divided into two groups: experimental and controlled. An educational program was prepared according to the developed model, and two instruments consisted of a computer programming test in HTML, both theoretical and practical, and a self-efficacy measuring instrument. They were administered on both groups before and after the experiment. The results showed statistically significant differences between the two groups at the level (α = 0.05) in favor of the experimental group at all levels of the theoretical and practical achievement test, and also showed statistically significant differences between the two groups in favor of the experimental group at all levels of the self-efficacy scale. The study recommended the adoption of the developed generative model of the computer subject that the current study has used as well as the teaching guide prepared.